The Russian Minority on the Territory of the Former Soviet Republics (Czech Journal of International Relations, 1999)
The presence of Russians in the Euro-Asian area outside the territory of the present Russian Federation cannot be boiled down merely to a vestige of Soviet times and neither to the repercussions of the former existence of the Russian Empire. In many cases, Russians settled down in these parts even before they fell under the domination of the Russian state. On the other hand, the position of a national minority, living outside the borders of Russia in an independent and ethnically different country, is something new and unusual for the Russians; this applies to members of such a Russian minority as well as to Russians and Russian politicians within Russia.We can talk about the Russian minorities in a “narrower” or in a “wider” sense: in a “narrow sense” when referring to ethnic Russians, and in a “wider sense” when referring to large groups of people for whom Russian is the main language of communication. These are the Ukrainians and other Slavs outside their ethnic territory, various half-breeds, resettlers and even members of the local nationality who have accepted Russian as their first language.The question of the Russian minority in individual states is inseparable from the general, very strong historical, psychological and cultural ties of these new states to Russia, the Russian language and Russian culture. (This applies primarily to Belarus, Kazakstan, the Kirgiz Republic, and to some extent also to Ukraine and Turkestan). In these countries one cannot even refer to the Russians as a minority. On the grounds of the size of the Russian population and other “Russian-speaking” inhabitants, and the significance of the Russian language in the administration and life of society, they will for a long time remain bilingual and half-Russian.The situation in Latvia and Estonia is different; although the number of Russians there is considerable, they are pushed to the fringe of social life. In Lithuania, their integration in society and minority rights is far better. Moldova experienced a specific development as the country virtually broke up into a Slav and a Romanian part. Ethnic Russians accounted for a smaller percentage in Transcaucasia, in Lithuania, Uzbekistan and Tajikistan. Owing to their own cultural traditions, the Russian language did not make such inroads as in the other countries.